Qur'an translation : discourse, texture and exegesis. - Abdul-Raof, Hussein (Routledge, 2001)
The Qur'an is read by millions of Muslims on a daily basis, yet there is no book available to the reader, Arab or non-Arab, which provides a linguistic and rhetorical insight into Qur'anic discourse. This book explains Qur'an translational problems and provides a thorough account of the unique syntactic, semantic, phonetic, prosodic, pragmatic, and rhetorical features of the Qur'an.--Publisher's description
Originally published: Richmond: Curzon,1999
Keywords: Quran -- Translations